1987
DOI: 10.1007/bf00931436
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin levels in maternal and fetal plasma, amniotic fluid, and neonatal plasma and urine

Abstract: Oxytocin was measured in maternal and fetal plasma, amniotic fluid and neonatal plasma and urine using a specific radioimmunoassay, following extraction procedures with Florisil. Maternal oxytocin levels rose progressively with advancing gestation, but there were no significant differences between oxytocin levels around the onset of labor. No diurnal rhythm of oxytocin was evident in maternal plasma during the third trimester. Maternal and umbilical plasma oxytocin levels at spontaneous delivery were significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
46
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 15 publications
1
46
1
1
Order By: Relevance
“…Researchers studying 76 full-term infants found that plasma OT levels were lower at 4 days of life than at 0.5 hr of life, though the result was not statistically significant (Leake, Weitzman, & Fisher, 1981). Others found significantly lower plasma OT levels in term infants at 7 versus 2 days of life (Kuwabara et al, 1987). Future research is needed to find physiologic explanations for the maturational decrease in plasma OT levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers studying 76 full-term infants found that plasma OT levels were lower at 4 days of life than at 0.5 hr of life, though the result was not statistically significant (Leake, Weitzman, & Fisher, 1981). Others found significantly lower plasma OT levels in term infants at 7 versus 2 days of life (Kuwabara et al, 1987). Future research is needed to find physiologic explanations for the maturational decrease in plasma OT levels.…”
Section: Discussionmentioning
confidence: 99%
“…OT is present in human fetal brain tissues as early as 14 weeks gestation, and its levels significantly increase throughout the course of gestation in areas of the brain such as the pituitary and the hypothalamus (Burford & Robinson, 1982). Investigators have not measured OT longitudinally in fetal umbilical plasma, but cross-sectional measurements have been successful in fetuses near the time of labor (Kuwabara, Takeda, Mizuno, & Sakamoto, 1987). In healthy, term human infants, OT is measurable in plasma (Kuwabara et al, 1987), urine (White-Traut, Powlesland, Gelhar, Chatterton, & Morris, 1998), saliva (Feldman, Gordon, & Zagoory-Sharon, 2010), and cerebral spinal fluid (CSF; Clark et al, 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Oxytocin release increases during labor and lactation. However, oxytocin release decreases at cesarean delivery compared to vaginal delivery [24,25]. Moreover, oxytocin has shown anti-proliferative effects in several cancers as well as in breast cancer cells [2628].…”
Section: Discussionmentioning
confidence: 99%
“…Parturition is an important developmental time-point with exposure to high levels of maternal OXT (Kuwabara et al, 1987; Douglas et al, 2002; Tyzio et al, 2006; Khazipov et al, 2008; Mazzuca et al, 2011). Prenatal binding of this OXTR ligand has not been examined in the whole embryo.…”
Section: Discussionmentioning
confidence: 99%